Film's musical moments - Conrich, Ian; Tincknell, Estella (Music and the moving image., 2006)
The scope of this collection is indicative of the breadth and diversity of music's role in cinema, as is its emphasis on musical contributions to 'non-musical' films. By bringing together chapters that are concerned both with the relationship between performance, music and film and the specificity of national, historical, social, and cultural contexts, Film's Musical Moments will be of equal importance to students of film studies, cultural studies and music. The book is organised into four sections: Music, Film, Culture focuses on cinema representations of music forms; Stars, Performance and Reception explores stars, fan cultures and intertextuality; The Post-Classical Hollywood Musical considers the importance of popular music to contemporary cinema; and Beyond Hollywood looks to specific national contexts. Chapters include jazz and animation, the Country and Western biopic, cult musicals and fandom, the importance of the soundtrack movie, and musicals from the former East Germany.